Music, neurology, and neuroscience : evolution, the musical brain, medical conditions, and therapies - Altenmuller, Eckart; Finger, Stanley; Boller, Francois (Progress in brain research, 2015)
Did you ever ask whether music makes people smart, why a Parkinson patient's gait is improved with marching tunes, and whether Robert Schumann was suffering from schizophrenia or Alzheimer's disease? This broad but comprehensive book deals with history and new discoveries about music and the brain. It provides a multi-disciplinary overview on music processing, its effects on brain plasticity, and the healing power of music in neurological and psychiatric disorders. In this context, the disorders the plagued famous musicians and how they affected both performance and composition are critically.